The use of the GLP-1 analog - dulaglutide in the treatment of morbid obesity - case report - Juda, Agata; Rojek, Kornelia; Kamińska, Magdalena; Strzoda, Adam; Polak, Agnieszka (Journal of Education, Health and Sport, 2022)
Obesity is a disease that is diagnosed in an increasing number of people around the world. Its development is influenced by many factors, both environmental and genetic. It leads to the development of further diseases, thus contributing to a reduction in life expectancy. There are many methods used to treat overweight and obesity. The most important element of the therapeutic process is a reduced diet and physical activity. However, it is often not sufficient, therefore it is becoming more and more common to introduce pharmacotherapy into treatment. One drug is dulaglutide (Trulicity), a GLP-1 analog with promising results. It was included in the treatment of a 49-year-old patient who was diagnosed with morbid obesity. The patient had been struggling with obesity since childhood, and the previously used methods of weight reduction did not bring satisfactory results. After switching to Trulicity (1.5 mg / 0.5 mL s.c.) taken once a week, it was possible to achieve a significant decrease in body weight and the well-being of the patient. If it is officially registered in the treatment of this disease in the future, there is a chance that the results of therapy will improve in many patients.